Randomized clinical trial of deep brain stimulation for poststroke pain. Issue 5 (May 2017) - Lempka, Scott F.; Malone, Donald A.; Hu, Bo; Baker, Kenneth B.; Wyant, Alexandria; Ozinga, John G.; Plow, Ela B.; Pandya, Mayur; Kubu, Cynthia S.; Ford, Paul J.; Machado, Andre G.
Abstract : Objective: The experience with deep brain stimulation (DBS) for pain is largely based on uncontrolled studies targeting the somatosensory pathways, with mixed results. We hypothesized that targeting limbic neural pathways would modulate the affective sphere of pain and alleviate suffering. Methods: We conducted a prospective, double‐blinded, randomized, placebo‐controlled, crossover study of DBS targeting the ventral striatum/anterior limb of the internal capsule (VS/ALIC) in 10 patients with poststroke pain syndrome. One month after bilateral DBS, patients were randomized to active DBS or sham for 3 months, followed by crossover for another 3‐month period. The primary endpoint was a ≥50% improvement on the Pain Disability Index in 50% of patients with active DBS compared to sham. This 6‐month blinded phase was followed by an 18‐month open stimulation phase. Results: Nine participants completed randomization. Although this trial was negative for its primary and secondary endpoints, we did observe significant differences in multiple outcome measures related to the affective sphere of pain (eg, Montgomery–Åsberg Depression Rating Scale, Beck Depression Inventory, Affective Pain Rating Index of the Short‐Form McGill Pain Questionnaire). Fourteen serious adverse events were recorded and resolved. Interpretation: VS/ALIC DBS to modulate the affective sphere of pain represents a paradigm shift in chronic pain management. Although this exploratory study was negative for its primary endpoint, VS/ALIC DBS demonstrated an acceptable safety profile and statistically significant improvements on multiple outcome measures related to the affective sphere of pain. Therefore, we believe these results justify further work on neuromodulation therapies targeting the affective sphere of pain. Ann Neurol 2017;81:653–663